Reasons for Students’ Code-Switching Between Informal Indonesian and English in ELT Contexts - Marwa Marwa (ELT-Lectura, 2014)
This descriptive and analytical study aimed at exploring the phenomenon of code-switching between Informal Indonesian (INF-I) and English exhibited in the classroom speech of the students at English Education Department of Faculty of Education and Teachers Training Lancang Kuning University in Pekanbaru-Riau. The main discussion of code-switching (CS hereafter) is the students’ reasons for employing CS. The data was collected by recording the students’ speech which was then transcribed as conversational data and by conducting unstructured interview. The research was conducted particularly in formal situations; in Speaking I classes involving sixty students of the first year. This study found that in formal situations such as in ELT contexts, the students’ reasons for CS were as compensatory strategy for the deficiency, as a language negotiation, as extended explanation, as an expression of solidarity, as flexibility of expression and as translation. These all reasons were primarily pertinent to fulfill communicative needs and communicative strategies.